Effects of CoCl(2)-simulated hypoxia on the expression levels of matrix metalloproteinases in renal adenocarcinoma cells and renal tubular epithelial cells - Zhang, Xiaoyi (Exp Ther Med, 2018)
Renal cell carcinoma (RCC) and chronic kidney disease (CKD) are associated with hypoxia, but the effects of hypoxia on the process of angiogenesis in the two diseases are dramatically different. Some of matrix metalloproteinases (MMPs), such as MMP2 and MMP9, may have a role because they represent the most prominent family of proteinases associated with angiogenesis. In the present study, the differential response of human renal cell cancer cells (786-0), human renal tubular epithelial cells (HK-2) and human microvascular endothelial cells (HMEC-1) to hypoxia with regards to the expression of MMP2, MMP9, MMP14, TIMP2, RECK was investigated. Cobalt chloride (CoCl(2)) treatment was used to simulate the hypoxia environment in RCC and CKD. The expression levels of HIF-1α, RECK, MMP2, MMP9, MMP14 and TIMP2 in HK2, 786-0 and HMEC-1 cells were determined by western blot analysis after incubation with varying concentrations of CoCl(2) for 24 h. It was indicated that the effects of hypoxia on the endogenous expression of RECK and MMP2 differed depending on the considered cell type. Notably, the RECK expression was significantly decreased in 786-0 cells under hypoxia, whereas this expression was slightly increased in HK2 and HMEC-1 cells. Furthermore, the MMP2 expression was significantly increased in HMEC-1 cells under hypoxia, whereas the expression was slightly decreased in HK2 and 786-0 cells. These results demonstrate that 786-0, HK2 and HMEC-1 cells respond differently under hypoxic conditions. Furthermore, MMP2 and RECK may serve divergent roles in HK2 and HMEC-1 cells under hypoxic conditions.